Causes of Sudden Natural Death in Adults: A Retrospective Study from Malatya Province, Turkey - Senel, Fatma; MÄ±zrak, BÃ¼lent (Annals of Pathology and Laboratory Medicine, 2018)
Background: This studyâ€™s goal is to determine the incidence of sudden natural death (SND) based on adult forensic autopsies performed in the Turgut Ã–zal Medical Center Research Hospital, its age and gender distribution, and its causes and to evaluate histopathological results from the Â organs. Methods: Forensic autopsies from the last 1.5 years were examined retrospectively. Cases of sudden natural death over the age of 15 years were included. The ages and genders of the cases were recorded. Hematoxylin-Eosin stained preparations of organs were examined. The histopathological findings of the heart, lung, liver, kidney, and brain were evaluated. Conclusions: Sudden natural death was more common in older males. The most common cause was ischemic heart disease. Other causes included non-ischemic heart disease, respiratory system disease, central nervous system disease, gastrointestinal system disease, and urogenital system disease.